Systemic Thrombolysis Versus Device Exchange for Pump Thrombosis Management: A Single-Center Experience. Issue 3 (May 2016) - Oezpeker, Cenk; Zittermann, Armin; Ensminger, Stephan; Kizner, Lukas; Koster, Andreas; Sayin, Ali; Schoenbrodt, Michael; Milting, Hendrik; Gummert, Jan F.; Morshuis, Michiel
Abstract : In patients with left ventricular assist device (LVAD) implants, pump thrombosis is a potential life-threatening complication. In a retrospective data analysis, we compared clinical outcomes in 50 patients with HeartWare (HW) or HeartMate II implants undergoing device exchange (DEx; n = 21) or systemic thrombolysis (STL; n = 29) for pump thrombosis. Primary end-point was survival up to 90 days postintervention. Secondary end-points were the need for blood products postintervention, duration of intensive care unit stay, in-hospital stay, 90 day and 2 year therapy failure (the need for additional surgical or nonsurgical intervention because of pump thrombosis), and 2 year survival. Ninety-day survival was 89.3% in the STL group and 91.0% in the DEx group ( p = 0.901). Compared with the DEx group, the average use of different blood products was lower ( p < 0.001), and duration of intensive care unit stay and in-hospital stay tended to be shorter in the STL group ( p values = 0.086 and 0.048, respectively). However, 90 day freedom from therapy failure was significantly lower in the STL group than in the DEx exchange group ( p = 0.027) and so was 2 year freedom from therapy failure ( p = 0.006). Two-year survival was comparable between groups ( p = 0.267). Our data indicate that STL can be considered as a therapeutic option in LVAD patients with pump thrombosis.